THE ANALYSIS OF DIASTASIS RECTI INCIDENCE IN POSTPARTUM WOMEN IN MOJOKERTO CITY - Lasiyati Yuswo Yani (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Diastasis recti abdominis is a condition in which the rectus abdominis muscles separate in the midline at the linea alba. It is currently unknown whether this is a true separation or tissue relaxation. The purpose of this study was to analyze the incidence of distasis recti in postpartum mothers and assessing the severity of distasis recti experienced by the mother. Method research in study This is descriptive quantitative with use cross-sectional approach. Subject study determined by purposive sampling, namely integrated health post at the Community Health Center (UPT) Minister and UPT Puskesmas Kranggan. Election location This done with consideration postpartum mothers data cutoff until with June 2025 two community health center have coverage most postpartum mothers first and second in Mojokerto City. Data collection was carried out with observation inspection physical. Sample study This only conducted at 6 integrated health posts with amount sample amounting to 64 people. The data was analyzed in a way univariate. Research results Research results show that 56% of mothers postpartum experienced abdominal diastasis recti and 26% of them had moderate diastasis recti. The symptoms experienced by 67% of respondents were pain.